Modelling bristle bending in brush seals - Howell, P; Lattimer, T (1999)
Brush seals in turbine engines offer a potential increase in efficiency relative to labyrinth seals, and the response of the bristles to the aerodynamic forces is an important factor in their performance. In some respects the behaviour of a single bristle gives a good indication of the seal behaviour. Here, we examine the single bristle problem using linear beam theory and Coulomb friction with a view to understanding the phenomenon of "locking". The bristle is subject to a force at one end, and part of the bristle is constrained to lie above a plane normal to this force. It is found that for any coefficient of friction, the bristle will always be deflected from a straight line configuration, and that thereafter only a small change in force is needed to overcome the friction. In addition, a closed-form expression for the deflection of the bristle is determined.